Benarkah Pembiayaan Murabahah Berpengaruh Terhadap Profitabilitas - Muji Lestari, Uun Tri; Cahyono, Hendry (Jurnal Ekonomika dan Bisnis Islam, 2019)
This study aims to determine how much the influence of murabahah financing on profitability in KSPPS BMT Mandiri Sejahtera East Java. This study describes a quantitative research using a descriptive quantitative approach. The data used by the researcher are primary with interview methods and secondary in the form of balance sheets and profit and loss for the period 2009-2018, yearly. For the population and sample, the researcher uses secondary data in the form of balance sheets and income statements for the period 2009-2018 per year. The analysis technique which is used in this research is the simple linier regression. The result of this study state that partial test (t) present that murabahah financing does not significantly influence the profitability. The result of the determination coefficient test (R2) indicate that murabahah financing effects profitability of 0.7%, while the remaining 99.3% is influenced by other variables not examined.